The Role of Brand Awareness in Mediating the Effect of Social Media Campaign on Purchase Intention - Hasan, Tity Alayda; Haji, Sulfi Abdul; Mohungo, Yolanda (International Journal of Business, Law, and Education, 2025)
This study aims to analyze the role of Brand Awareness in mediating the effect of Social Media Campaigns on Purchase Intention for Warner Bros. movie marketing in Indonesia. Specifically, this research examines the intention to purchase movie tickets from Warner Bros. as a production house. This research was conducted through quantitative approach with a total of 110 respondents who have certain criteria, namely aged 17 to 50 years, social media users (Instagram, X, Tiktok, and Facebook), and have watched movies produced by Warner Bros. The data was processed using the Structural Equation Modelling with the Smart Partial Least Square statistical program. The results of this study prove that: Social Media Campaign has a significant effect on Purchase Intention; Social Media Campaign has a significant effect on Brand Awareness; Brand Awareness has a significant effect on Purchase Intention; and Brand Awareness mediates the effect of Social Media Campaign on Purchase Intention.